Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Mobil Honda (Studi Kasus Pada PT. Nusantara Mobil Internasional Cabang Bekasi) - Geo Widantoro Putro; Diana Prihadini (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine the effect of product quality and price on purchasing decisions for Honda cars (Case study at PT. Nusantara Mobil International Bekasi branch). The research method used is a quantitave method. Data collecting technique used is in the form of questionnaires and literature. The population of this research is users/buyers of Honda cars at PT. Nusantara Mobil International Bekasi branch. The sampling technique in this study is non-probablity sampling with accidental sampling method. Samples are 85 samples. The data analysis used is multiple linear regression analysis using the help of IBM Statistics Software version 24. The results showed the effect of product quality had an influence on purchasing decisions for Honda cars by 40,5%. Meanwhile price has and effect of 48,4% on purchasing decisions for Hnda cars. The variables of product quality and price affecr the purchasing decision variable simultaneously with a value of 52%. Product quality and price have a significant effect on purchasing decisions for Honda cars at PT. Nusantara Mobil International Bekasi Branch.